2015
DOI: 10.1016/j.fcr.2015.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Improved nursery management further enhances the productivity of stress-tolerant rice varieties in coastal rainfed lowlands

Abstract: a b s t r a c tThe productivity of rice in most tropical coastal areas of Asia is low because of the predominance of several abiotic and biotic stresses, use of long duration traditional landraces or old varieties and suboptimal management practices. A combination of high-yielding, stress-tolerant rice varieties and good management practices is necessary to enhance the productivity of these areas. Suboptimal nursery management using traditional methods practiced in these areas often leads to a reduced plant po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(23 citation statements)
references
References 26 publications
3
19
1
Order By: Relevance
“…Many research studies have shown that the use of younger seedlings (not older than 25 d old) produced positive impacts on grain yield [21][22][23], although many authors have also contradicted this [24][25][26]. In our study, a significant SA × V interaction on grain yield was found in both years.…”
Section: Discussionsupporting
confidence: 44%
“…Many research studies have shown that the use of younger seedlings (not older than 25 d old) produced positive impacts on grain yield [21][22][23], although many authors have also contradicted this [24][25][26]. In our study, a significant SA × V interaction on grain yield was found in both years.…”
Section: Discussionsupporting
confidence: 44%
“…Rice cultivation in SSA is seriously undermined not only by nutrient-deficient soils but also by abiotic stresses at the initial growth stage (Seck et al, 2013). In this respect, the improvement of seedling quality by optimizing nutrient management in the nursery has been documented as an effective measure to overcome abiotic stresses such as submergence (Bhowmick, Dhara, Singh, Dar & Singh, 2014;Ella & Ismail, 2006;Jackson & Ram, 2003;Ram et al, 2009;Singh, Hong, Sharma & Dhanapala, 2004), salinity (Sarangi et al, 2015), and drought stress (Ros et al, 2015). Panda, Reddy and Sharma (1991) demonstrated the large yield gains by 0.4-2.1 t ha −1 and AE N at 40-210 kg kg −1 with the nursery application of 100 kg N ha −1 (roughly equivalent to 10 kg N ha −1 in main field) at submergenceprone fields in the initial growth stage.…”
Section: Improvement Of Ae N With Small-dose Fertilizer Supplementationmentioning
confidence: 99%
“…Submergence tolerance in rice is highly dependent on several environmental conditions including temperature, irradiance during submergence, submergence depth (Palada and Vergara, 1972;Adkins et al, 1990;Singh et al, 2009), flood water CO 2 concentrations (Setter et al, 1987), as well as the physiological condition of the plant material such as age (Adkins et al, 1990, Sarangi et al, 2015, carbohydrate content and nutrient status (Jackson and Ram 2003;Singh et al, 2014a;Gautam et al, 2014aGautam et al, , 2014b. Additional doses of 20 and 30 kg post-flood N ha -1 applied 7-10 DAD significantly…”
Section: Survival and Growth Parametersmentioning
confidence: 99%
“…These varieties are being adopted on a large scale in South Asia, given that they retain their other main agronomic and quality traits (Xu et al, 2006;Neeraja et al, 2007;Singh et al, 2009Singh et al, , 2011Singh et al, , 2014bSeptiningsih et al, 2009). However, tolerance level and productive potential of such newly released varieties can be further enhanced through matching crop and nutrient management (Ismail et al, 2013;Bhowmick et al, 2014;Singh et al, 2014a, Sarangi et al, 2015.…”
Section: Chlorophyll Concentrationmentioning
confidence: 99%